LEGAL POLITICS OF THE GENERAL ELECTION SYSTEM IN INDONESIA TO REALIZE DEMOCRATIC GENERAL ELECTIONS - Rizkia Dwi Oktadini; Hartati; Zarkasi (CV. RADJA PUBLIKA, 2025)
The purpose of this study is to find out and analyze the arrangement of the general election system in Indonesia and to find out and develop the general election system in Indonesia in order to realize democracy. The research method used in writing this research is the normative legal research method.The research results explain thatthe general election system which was initially implemented in 1955 until nowIndonesia already has quite complex legal regulations and is felt to have formulated important things that serve as guidelines for implementing elections.And the implementation of democratic principles in general elections in Indonesia in the perspective of legal politics. In the perspective of legal politics, these principles have a strong basis in the Indonesian legal system. The suggestion in this study is that in the future the regulation of the general election system used for the next general election will continue to emphasize the values ​​of the constitution and the 1945 Constitution. And not ignore the values ​​of democracy and sovereignty. The general election system implemented in Indonesia in the future depends on the objectives and priorities of the election itself and also depends on Indonesia's readiness as a democratic country. In determining the general election system in Indonesia in the future, it is important to carefully consider the impacts of the systems used and compare them with the needs and ideals of the Indonesian nation.